Analisis Pembangkit Listrik Tenaga Surya (PLTS) Sistem On - Grid Untuk Memenuhi Kebutuhan Listrik Base Transceiver Station (BTS) di Desa Sabi Samukop Kepulauan Mentawai - Riyan siyentanu mareat Sakeru; Eva Magdalena Silalahi; Robinson Purba (Prodi Teknik Elektro FT UKI, 2023)
PLTS is a renewable energy source because it uses solar power as its energy source. Solar photovoltaic captures the sun's heat and converts it into electrical energy which can be stored in batteries and can also be used directly. The PLTS system used in this study is an on-grid hybrid system, by utilizing excess PLTS energy to be sold to the PLN grid. From the results of data analysis and simulation of the HOMER software that has been carried out, it is obtained that the electrical energy needed by the BTS is 3.96 kWh/day and the PLTS capacity is 1.3 kW with a production of electrical energy of 5.06 kWh/day. Based on the scenario or configuration of the on-grid hybrid PLTS system without batteries with a Net Present Cost (NPC) value of IDR 56,948,220.00, Levelized Cost of Energy (LCOE) IDR 1,144.39/kWh and Break Even Point (BEP) is reached after 3.3 years of project operation. Based on the simulation results, in terms of the economy and the electrical energy produced by the on-grid hybrid PLTS without batteries, it is considered appropriate to meet the electricity needs of BTS Saibi Samukop Village in the Mentawai Islands.